Internalization of Islamic Education Values in the Book of Bidayat al Hidayah to Develop the Religious Character of Santri - Janatun Firdaus; Uus Ruswandi; Asis Saefuddin; Mahrus As’ad (Green Publisher Indonesia, 2024)
ABSTRACT Background: The Islamic boarding school as a place of education and study of Islamic sciences, is also a place for developing the character of students. One of these efforts is through internalizing the values of Islamic education in the book of Bidayat al Hidayah to develop the religious character of students Purpose: The purpose of this study is to analyze the Program, Process, Evaluas, Supporting and inhibiting factors of the impact of internalizing Islamic educational values in the book of Bidayat al Hidayah to develop the religious character of students in Islamic boarding schools Method: The method used in this study is the descriptive-analytical method Results: The results showed that the internalization program of Islamic educational values in the book of Bidayat al Hidayah in Islamic boarding schools was carried out through creed formation programs, worship formation and moral formation. By indicators of having a wise attitude, courageous, maintaining self-chastity and fairness Conclusion: Based on the results of the study, it can be concluded that the internalization program of Islamic educational values in the book of Bidayat al Hidayah consists of a creed formation program, a worship formation program and a moral formation program